DEFINITION OF THE CATEGORY OF ORGANIZATIONAL AND ECONOMIC MECHANISM IN THE CONTEXT OF THE ECONOMIC MECHANISMS DESIGN THEORY - М. О. Кравченко; Т. В. Камінська (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut")
The article defines the essence of the category of organizational-economic mechanism in the context of the theory of designing economic mechanisms, developed by the Nobel Prize laureate L. Hurvicz and later supplemented by E. Maskin and R. Meyerson. A comparative analysis of the category of economic mechanism, organizational mechanism, organizational and economic mechanism is carried out in terms of systemic, process, and resultant approaches. The author's definition of the concept of organizational and economic mechanism is provided. Mechanisms are defined as a system of interconnected economic tools, processes, rules, and structures that are formalized and ensure the organization and coordination of economic activity to achieve desired goals that take into account the interests of the participants in the environment in which this mechanism is applied. A mathematical model describing this category in the context of the economic mechanisms design theory is presented. The prospects of using the approach proposed by L. Нurvicz for the study of the organizational and economic mechanism of interaction of the health care enterprises are determined.